Hawks vs. Doves: ECB's monetary policy in light of the Fed's policy stance - Niko Hauzenberger; Florian Huber; Thomas Zörner (Oesterreichische Nationalbank (OeNB), 2023)
The secular increase in globalization led to a substantial increase in the interconnectedness of global financial markets. This has important implications for the conduct of monetary policy, as central bank policies may diverge across countries, potentially affecting key transmission channels of domestic policy actions. In this paper, we use a non-linear multivariate time series model to shed light on how the US monetary policy stance affects the conduct of monetary policy in the euro area. We assume that the dynamic coefficients implicitly depend on a measure of the Federal Reserve's policy stance through a smooth transition function. This assumption allows us to examine how the dynamic responses of financial market quantities such as government bond yields and inflation swaps to euro area monetary policy shocks change with the US policy stance. Scenario-specific impulse responses show that the transmission of euro area monetary policy through financial markets does indeed depend on the prevailing monetary policy regime of the Federal Reserve and has significant effects on a variety of euro area variables.
Keywords: E43; E52; F42; G12; 330; Monetary Policy Transmission; Financial Markets; Real Rates; High-Frequency Data; Smooth Transition VAR